2015
DOI: 10.1039/c5ra01950h
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in quantum dot based sensors

Abstract: Recent progress in quantum dot (QD) based chemo- and biosensors for various applications is summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 131 publications
1
37
0
Order By: Relevance
“…Because of the presence of both AuNP and GO, the Raman signals of the dyes were drastically enhanced, leading to simultaneous ultrasensitive detection of two specific DNAs with excitation from a single light source . Quantum dots (QDs), semiconductor nanomaterials that show quantum mechanical properties, are another class of prevailing nanoparticles for the fabrication of biosensors for both in vitro and in vivo applications . QDs with different emission colors were used to conjugate with two ssDNAs that target two genes of a highly pathogenic bacterium.…”
Section: Photoluminescence Architectures: Simple Construction and DIVmentioning
confidence: 99%
“…Because of the presence of both AuNP and GO, the Raman signals of the dyes were drastically enhanced, leading to simultaneous ultrasensitive detection of two specific DNAs with excitation from a single light source . Quantum dots (QDs), semiconductor nanomaterials that show quantum mechanical properties, are another class of prevailing nanoparticles for the fabrication of biosensors for both in vitro and in vivo applications . QDs with different emission colors were used to conjugate with two ssDNAs that target two genes of a highly pathogenic bacterium.…”
Section: Photoluminescence Architectures: Simple Construction and DIVmentioning
confidence: 99%
“…Our previous studies have showed that QDs have unique optical and electronic properties such as size-tunable light emission, superior signal brightness, resistance to photobleaching and simultaneous excitation of multiple fluorescence colors. [25][26][27] QDs have gained broad application in many areas of biology. 28 The versatile properties of QDs have allowed investigators to conduct biological studies with extended spatiotemporal capabilities.…”
mentioning
confidence: 99%
“…This allows for a considerable reduction in manufacturing expenditures and is therefore very attractive for industrial purposes. Other than their emissive properties, they can also be used for a variety of other applications like in sensing devices, photovoltaics and more . Thus, colloidal QDs have been actively pursued for both fundamental research and industrial development due to their solution processability and size‐dependent optical properties associated with quantum confinement.…”
Section: Introductionmentioning
confidence: 99%